2001
DOI: 10.1182/blood.v97.8.2440
|View full text |Cite
|
Sign up to set email alerts
|

ARG tyrosine kinase activity is inhibited by STI571

Abstract: The tyrosine kinase inhibitor STI571 inhibits BCR/ABL and induces hematologic remission in most patients with chronic myeloid leukemia. In addition to BCR/ ABL, STI571 also inhibits v-Abl, TEL/ABL, the native platelet-derived growth factor (PDGF)␤ receptor, and c-KIT, but it does not inhibit SRC family kinases, c-FMS, FLT3, the epidermal growth factor receptor, or multiple other tyrosine kinases. ARG is a widely expressed tyrosine kinase that shares substantial sequence identity with c-ABL in the kinase domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
132
0
4

Year Published

2003
2003
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(142 citation statements)
references
References 31 publications
6
132
0
4
Order By: Relevance
“…Imatinib mesylate (STI571, Glivec s , Gleevec s -Novartis, Basel, Switzerland) is a potent competitive inhibitor of the tyrosine kinases associated with ABL Druker et al, 1996), KIT (Buchdunger et al, 2000;Heinrich et al, 2000), PDGFr (Buchdunger et al, , 2000 and ARG (Okuda et al, 2001), which impedes the interaction of ATP with the SH1 domain of these proteins (Schindler et al, 2000), thereby inhibiting the phosphorylation of downstream target proteins. Imatinib is a phenylaminopyrimidine derivative and represents the first of a new class of drugs known as signal transduction inhibitors.…”
mentioning
confidence: 99%
“…Imatinib mesylate (STI571, Glivec s , Gleevec s -Novartis, Basel, Switzerland) is a potent competitive inhibitor of the tyrosine kinases associated with ABL Druker et al, 1996), KIT (Buchdunger et al, 2000;Heinrich et al, 2000), PDGFr (Buchdunger et al, , 2000 and ARG (Okuda et al, 2001), which impedes the interaction of ATP with the SH1 domain of these proteins (Schindler et al, 2000), thereby inhibiting the phosphorylation of downstream target proteins. Imatinib is a phenylaminopyrimidine derivative and represents the first of a new class of drugs known as signal transduction inhibitors.…”
mentioning
confidence: 99%
“…The first of these to be developed was imatinib, a 2-phenylaminopyrimidine that inhibits the activity of BCR-ABL and, to varying degrees, several other tyrosine kinases. [5][6][7][8] Imatinib induces durable responses, prolongs event-free and progression-free survival in patients with CML, and is the current standard of care for this disease. 9,10 Imatinib has activity in all phases of CML, but the most extensive and durable responses are seen in chronic-phase patients, particularly those newly diagnosed with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal structure studies have revealed that imatinib binds to the kinase domain of ABL in its inactive conformation and therefore locks it in an inactive state [43,44]. Imatinib inhibits not only ABL but also the receptor for platelet-derived growth factor A and B (PDGFR-α, β), stem cell factor receptor (KIT) and ARG (abl-related gene) tyrosine kinases, making it useful in attenuating oncogenic events triggered upon activation of these kinases [45][46][47]. Imatinib appears to selectively induce apoptosis in numerous BCR-ABL-positive leukemic cell lines and BCR-ABL-transduced hematopoietic cells (BaF3 and 32D), but not in BCR-ABL-negative hematopoietic cancer cell lines (HL60, Jurkat and U937), or non-transformed growth factordependent hematopoietic cells.…”
Section: The Tyrosine Kinase Activity Of Bcr-abl and Avenues For Therapymentioning
confidence: 99%